Analisis Retaknya Crankshaft pada Auxiliary Engine Mv. Manalagi Tisya Menggunakan Fault Tree Analysis - Robbi, Shofa Dai; Danuaga, Anak Agung Gede Agung; Seno, Abdi; Kristiyono , Antonius Edy; Prawoto, Agus; Fitriani, Rika (Politeknik Negeri FakFak, 2025)
The crankshaft is a vital component of an engine that converts the linear motion of the piston into rotational motion to produce mechanical power for electricity generation. This study employs a descriptive qualitative method, utilizing data collection techniques such as observation, interviews, and literature review. The objective of this research is to analyze the factors contributing to the occurrence of cracks in the crankshaft of a diesel engine used as a generator prime mover. The findings indicate that the cracks are primarily caused by contamination of the lubricating oil with water, resulting from leakage in the lubricating oil cooler or tube oil cooler. Another contributing factor is the loosening of the connecting rod bolts, which may occur if they are not tightened to the specified torque or if a torque wrench is not used during installation. Corrective measures undertaken include replacing the gasket, repairing or replacing the leaking tube oil cooler, and retightening the connecting rod bolts using a torque wrench in accordance with the manufacturer’s specifications.